ANALISIS PESAN DAKWAH DALAM FILM USTADZ MELINEAL - Hendar Ardiansyah; Moh Syahri Sauma (An-Nida' : Jurnal Komunikasi dan Penyiaran Islam, 2024)
The “Ustadz Millenial” Web Series tells a life story about the life of a young man who aspires to become a young cleric. However, the problems and death of his family are his dreams. But he still tries to realize his goals by preaching through social media. Based on the above background, the purpose of this study is to answer how the signifiers and objects (references) displayed in the “Ustadz Milenial” series and what are the da'wah messages contained in the “Ustadz Milenial” series. In its analysis, this research uses a qualitative approach with Ferdinand de Saussure's semiotic method which focuses on the signifier and the sign and the object (referent). The data studied are in the form of pieces of images, texts, sounds, or voices contained in the “Ustadz Millenial” series. The results of the study show that the “Millennial Ustadz Series” is full of da'wah messages, including; invitations to be patient, forgive each other, maintain silahturahmi, try and endeavor, keep fifteen, be devoted to both parents, preach through social media that develops with technology in today's era, and display the hijab as advice to cover the aurat. The conclusion of this research is that the Ustadz Millennial Web Series has many valuable da'wah messages that represent aspects of aqidah, sharia, and morals. Overall, the Ustadz Millennial Web Series contains invitations to be patient, help each other, forgive each other, say and answer greetings, and display the use of the hijab as a recommendation to cover parts of the body that should not be seen (according to Islam) and mosques as certain symbols for carrying out congregational prayer services.